Subjective vs Objective Accommodative Amplitude: Preschool to Presbyopia - Anderson, Heather A. (Optom Vis Sci, 2014)
PURPOSE: This study compared subjective and objective accommodative amplitudes to characterize changes from preschool to presbyopia. METHODS: Monocular accommodative amplitude was measured with three techniques in random order (subjective push-up, objective minus lens stimulated, and objective proximal stimulated) on 236 subjects 3–64 years using a 1.5mm letter. Subjective push-up amplitudes were the dioptric distance at which the target first blurred along a near-point rod. Objective minus lens stimulated amplitudes were the greatest accommodative response obtained by Grand Seiko autorefraction as subjects viewed the stimulus at 33cm through increasing minus lens powers. Objective proximal stimulated amplitudes were the greatest accommodative response obtained by Grand Seiko autorefraction as subjects viewed the stimulus at increasing proximity from 40cm up to 3.33cm. RESULTS: In comparison with subjective push-up amplitudes, objective amplitudes were lower at all ages, with the most dramatic difference occurring in the 3–5 year group (subjective push-up = 16.00 ± 4.98D versus objective proximal stimulated = 7.94 ± 2.37D and objective lens stimulated = 6.20 ± 1.99D). Objective proximal and lens stimulated amplitudes were largest in the 6–10 year group (8.81 ± 1.24D and 8.05 ± 1.82D, respectively) and gradually decreased until the fourth decade of life when a rapid decline to presbyopia occurred. There was a significant linear relationship between objective techniques (y = 0.74 + 0.96x, R(2) = 0.85, p<0.001) with greater amplitudes measured for the proximal stimulated technique (mean difference = 0.55D). CONCLUSIONS: Objective measurements of accommodation demonstrate that accommodative amplitude is substantially less than that measured by the subjective push-up technique, particularly in young children. These findings have important clinical implications for the management of uncorrected hyperopia.